Maldives-Assessment Letter for the Asian Development Bank and the World Bank. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The global crisis has hit the Maldivian economy hard; combined with an unsustainable fiscal expansion, it has led to a large fiscal deficit and severe balance of payments pressures. The authorities are committed to a strong policy adjustment program, and have requested IMF financial support for their program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet